Inhibitor‐3 ensures bipolar mitotic spindle attachment by limiting association of SDS22 with kinetochore‐bound protein phosphatase‐1. (8th October 2014) - Eiteneuer, Annika; Seiler, Jonas; Weith, Matthias; Beullens, Monique; Lesage, Bart; Krenn, Veronica; Musacchio, Andrea; Bollen, Mathieu; Meyer, Hemmo
Abstract Faithful chromosome segregation during mitosis is tightly regulated by opposing activities of Aurora B kinase and protein phosphatase‐1 (PP1). PP1 function at kinetochores has been linked to SDS22, but the exact localization of SDS22 and how it affects PP1 are controversial. Here, we confirm that SDS22 is required for PP1 activity, but show that SDS22 does not normally localize to kinetochores. Instead, SDS22 is kept in solution by formation of a ternary complex with PP1 and inhibitor‐3 (I3). Depletion of I3 does not affect the amount of PP1 at kinetochores but causes quantitative association of SDS22 with PP1 on KNL1 at the kinetochore. Such accumulation of SDS22 at kinetochores interferes with PP1 activity and inhibits Aurora B threonine‐232 dephosphorylation, which leads to increased Aurora B activity in metaphase and persistence in anaphase accompanied with segregation defects. We propose a model in which I3 regulates an SDS22‐mediated PP1 activation step in solution that precedes SDS22 dissociation and transfer of PP1 to kinetochores, and which is required for PP1 to efficiently antagonize Aurora B.